159 Mitigating Microglial-Mediated Neuroinflammation: The Sur1-Trpm4 Channel Regulates Calcium-Sensitive Induction of iNOS. (August 2015) - Kurland, David B.; Stokum, Jesse; Ivanov, Alex; Gerzanich, Volodymyr; Simard, J. Marc
Abstract : INTRODUCTION: Microglia, the resident immune cells of the central nervous system, play a critical role in health and disease. Following injury, microglia upregulate inducible nitric oxide synthase (iNOS), and can exert neurotoxic effects by releasing large quantities of nitric oxide (NO). Expression of iNOS, and many other proinflammatory genes, is regulated in part by Ca 2+ influx and Ca 2+ -dependent transcription factors. The expression of the nonselective cation channel Sur1-Trpm4 may be 1 molecular mechanism by which microglia dynamically modulate Ca 2+ influx. We hypothesized that microglial Sur1-Trpm4 plays a role in microglial-mediated neuroinflammation by regulating the calcium-sensitive induction of iNOS. METHODS: The Toll-like receptor 4 (TLR4) agonist lipopolysaccharide (LPS) was used as a stimulus to activate microglia. Protein expression was evaluated by immunohistochemistry, Western blot, and coimmunoprecipitation (Co-IP). Quantitative PCR (qPCR) was used to evaluate gene expression. Functional Sur1-Trpm4 activity was evaluated electrophysiologically. Confocal microscopy and the calcium-sensitive fluorescent dye, Fluo-4, was used to dynamically measure intracellular calcium. Extracellular nitrite, a by-product of NO formation, was measured to evaluate iNOS activity. RESULTS: Microglia express functional Sur1-Trpm4 channels, whose activity modulated Ca 2+ oscillations induced by TLR4 ligation. Inhibition of Ca 2+, Sur1-Trpm4 or NFAT all significantly abrogated the induction of iNOS. The activation of NFAT induced by TLR4 ligation was modulated by inhibition of Sur1. CONCLUSION: Our results strongly support our hypothesis that Sur1-Trpm4 regulates the calcium-sensitive induction of iNOS by controlling NFAT activity. These observations have impactful therapeutic implications. Inhibition of Sur1-Trpm4 using the well-tolerated sulfonylurea glibenclamide (a.k.a. glyburide) may be a promising approach to limit the deleterious effects of microglial-mediated neuroinflammation.